Multicultural Education in Indonesia: Meaning, Implications, and Context-Based Development Strategies - Zawil Huda; Edy Juarminson; Mahmoud Abderaman Hassane (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to examine the meaning and implications of multicultural education in Indonesia and to formulate context-based development strategies that are compatible with the nation’s unique socio-cultural, religious, and ideological characteristics. Indonesia’s extreme diversity, ethnic, linguistic, cultural, and religious, makes multicultural education not merely an option but a structural necessity for sustaining social cohesion and national integrity. Theoretical framework: The theoretical framework of this research integrates modern multicultural education theory, particularly James A. Banks’ five dimensions of multicultural education, with Islamic normative values such as ta‘āruf (mutual recognition), tasāmuḥ (tolerance), ‘adl (justice), and ukhuwah insāniyyah (human fraternity). This integrative framework positions Islam as a source of inclusive social ethics rather than an exclusive identity. Literature review: The literature review reveals that existing studies largely treat multicultural education either from a secular pedagogical perspective or from a normative religious approach, often without sufficient contextual adaptation to Indonesia’s plural yet Muslim-majority setting. This study addresses that gap by synthesizing multicultural theory, Islamic theology, and Indonesian socio-political realities. Methods: The research employs a qualitative descriptive-analytical design based on library research, analyzing academic literature, policy documents, national regulations, empirical reports, and Islamic primary sources. Data were examined using interactive analysis involving data reduction, thematic categorization, interpretation, and triangulation of sources and theories. Results: The findings demonstrate that multicultural education in Indonesia must be understood as a transformative educational process rather than mere tolerance instruction. Effective implementation requires integration across curricular, pedagogical, institutional, and digital dimensions. The study proposes context-based development models, including localized curricula, multicultural teacher training, inclusive school cultures, and digital literacy strategies to counter identity-based intolerance. Implications: The implications of this research are both theoretical and practical. Theoretically, it enriches Islamic education scholarship by demonstrating that multiculturalism is deeply rooted in Islamic theology. Practically, it offers policy-relevant recommendations for curriculum design, teacher education, and institutional governance. Novelty: The novelty of this study lies in its integrative and contextualized model that bridges universal multicultural values, Islamic ethical principles, and Indonesia’s national ideology, positioning multicultural education as a strategic instrument for social justice, national unity, and sustainable peace.